Reka bentuk perisian pembelajaran balaghah Arab peringkat sekolah menengah / Mohd Zulkhairi Abd Hamid - Mohd Zulkhairi, Abd Hamid (2012)
This study is related to learning balaghah in Form 4 Arabic language subject. The aims of this study are as follows: to design more effective and fun alternative method of learning balaghah, to identify the elements of multimedia used in designing balaghah learning software, and to evaluate the effectiveness of multimedia technology-based balaghah learning. The software designing process was based on the Arabic software development model structured using ASSURE instructional design model (Heinch et al., 1996) workflow guide. Mix-method approach was used in this study where 76 respondents from form four students of Maktab Mahmud, Alor Setar, Kedah, who were from three different academic streams, were involved. Three experts in the field of Arabic language also involved as respondents. This study employed survey method using 5-point Likert scale to collect the data. The data were analysed using statistical analysis assistance package, Statistical Package for the Social Sciences (SPSS). After the software designing process, a learning software module named “Balaghah Arab” was designed. By preparing storyboard, the specifications and functional uses of the multimedia elements in the “Balaghah Arab” module such as texts, graphics, animations, audio, and interactive could be explained. Furthermore, the results from the evaluation of “Balaghah Arab” software prototype showed that the multimedia technology-based balaghah learning was effective and satisfying. However, a few faults were identified in the “Balaghah Arab” software prototype. Some suggestions were also forwarded to the authoritative parties to enhance the quality of teaching and learning (T&L) in Arabic language.